Empowerment of Dasawisma Human Resources Through Higher Education Assistance in Effective Implementation of Administration - lilisuryani; Fatimah Fatimah; Sabariah Sabariah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
THis community service activity aims to enhance the human resource capacity of Dasawisma members in effective administration management as a family development data base at the sub-district level. The assistance was conducted using a participatory approach and hands-on practice, including socialization, technical administrative training, and reflective discussion. The results indicated an increase in Dasawisma members' understanding of the importance of orderly, systematic, and integrated administration in supporting social activities. Members' technical skills in managing family data, filling administrative books, classifying information, and preparing simple reports improved significantly. Furthermore, the assistance strengthened communication and coordination between Dasawisma and sub-district officials, promoted group independence, and strengthened Dasawisma's role as a key data source for family development. These findings confirm that planned and participatory higher education assistance plays a strategic role in community empowerment, supports good governance at the local level, and can serve as a replicable model for other community development programs.